Strategies for Recovery and Maintain of A Biped Walking Robot Balance - Pop, N; Vladareanu, L; Wang, H; Ungureanu, M; Migdalovici, M; Vladareanu, V; Feng, Y; Lin, M; P. Mastan, E; El Emary, Ibrahiem (International Journal of Engineering and Technology, 2018)
Recovering and maintaining the balance of the biped walking robots play an important role in their operation. In this article we will analyze some strategies for balancing in the sagittal plane, in the presence of external disturbances and changing the proportions between legâ€™s length and trunkâ€™s length (golden section), and/or adding weights (boot type) between the ankle and the knee so that the center of gravity is as low as possible. For equilibrium recovery, we suggest that the biped walking model be equipped with actuator that provides a torque at the hip. or/and at the ankle. The strategy of balance has a goal to move the disturbed system to the desired equilibrium state. We chose to study, the model of a double linear pendulum inverted under-actuated, with one passive and one active joint. Each case study and usage of these strategies is validated by Webots and is applied for NAO robot.Â